Impact of urban greening on microclimate and air quality in the urban canopy layer: Identification of knowledge gaps and challenges - Ernst, M.; Le Mentec, S.; Louvrier, M.; Loubet, B.; Personne, E.; Stella, P. (Frontiers in Environmental Science, 2022)
Growing urbanization leads to microclimate perturbations and in particular to higher temperatures inside the city as compared to its rural surroundings, a phenomenon known as the urban heat island. Although it exists at several scales, this study focused only on the urban canopy layer, where inhabitants live. A bibliometric study was performed to describe and understand the relationships between strategies of urban greening and canopy layer urban heat island modification in terms of air quality and microclimate. Science mapping of 506 bibliographical resources was performed through co-word and co-citation analysis. A subset of forty-four articles related to microclimate and air quality modelling was extracted and synthesized. This analysis showed scientific papers were polarized into microclimate or air quality studies without strong links between both, implying small collaboration between these fields. There is need for studies coupling microclimate and air pollution modelling to assess vegetation’s impacts at city scale.